Relationship of HHV8 serum levels and clinical features of Kaposi's sarcoma among patients in South Africa - Tibenderana, Rebecca (Division of Radiology, 2024)
Background. Kaposi's sarcoma is an AIDS-defining illness caused by Kaposi's Sarcomaassociated Herpesvirus (KSHV). The level of HIV immune suppression and extent of KSHV DNA determine the development of Kaposi's sarcoma. Common manifestations of Kaposi's sarcoma include skin and mucosa} involvement. lympboedema. and viscera] disease. Objectives. The purpose of this study was to explore the association between KSHV DNA viral load and clinical extent of Kaposi's sarcoma. Methods. This was a cross sectional study involving 100 patients with Kaposi sarcoma who attended Groote Schuur Hospital for treatment. The cohort had previously participated in a study investigating polymorphisms in the KSHV G-protein coupled receptor gene. KSHV viral load was determined by PCR of DNA extracted from peripheral blood mononuclear cells. Demographic and clinical data were collected. and logistic regression was applied to study association of KSHV viral load with the predominant presenting feature in patients with symptomatic KS. Results The cohort was predominantly male (63.16%) with a median age of 37.76 years. Median CD4 count was 235 cells/microlitre (64.0-418.0) and most patients (95.7%) had Tl disease. There was no association between KSHV DNA levels and clinical extent of Kaposi's sarcoma. Relative risk ratio (RRR) of l.006 (95% CI 0.974-1.006) p=0.174. Serum KSHV levels were not associated with outcome of treatment. however, patients who had poor outcomes had elevated KSHV levels. Conclusion. There was no relationship between KSHV viral load and clinical extent of Kaposi's sarcoma in this study. KSHV DNA viral load may be useful in predicting which patients will require aggressive treatment for Kaposi's sarcoma